KERONGSANG USANG : SECEBIS PENGALAMAN SEORANG PENGETUA - Shamsiah Ismail, 1953- (Wangsa Maju, Kuala Lumpur : Institut Terjemahan & Buku Malaysia Berhad, 2016)
Anecdotes of a school principal on administration and educational for students in Malaysia.
Keywords: Shamsiah Ismail, -- 1953- -- Anecdotes; School principals -- Anecdotes; Teachers -- Anecdotes; Educators -- Anecdotes; Anecdotes